2019
DOI: 10.21013/jems.v14.n3.p4
|View full text |Cite
|
Sign up to set email alerts
|

Drugs and Substance Abuse among the Secondary School Students in Korogocho: Implications for Behaviour and Performance

Abstract: <p>Globally, Drugs and substance abuse continues to be a challenge, especially among the youth in school and out of school. It impacts negatively on the academic, social psychological and physical development among the abusers. This paper examines the effects of drugs and substance abuse on social conduct and academic performance among the students as well as the mitigating measures. It is based on a study carried out at Korogocho slums. A total of 102 students and 15 key informants were sampled.  Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Fenomena penyalahgunaan narkoba pada pelajar tidak hanya merupakan masalah individu, tetapi juga mencerminkan gap yang ada dalam sistem pendidikan dan sosial. Salah satu fenomena yang mencolok adalah kurangnya pemahaman dan kesadaran akan bahaya narkoba di kalangan pelajar (Ondigo et al, 2019). Banyak di antara mereka yang terpengaruh oleh budaya populer atau teman sebaya yang mempromosikan penggunaan narkoba sebagai sesuatu yang keren atau menghibur tanpa memperhatikan risiko yang terkait (Bano, 2021).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Fenomena penyalahgunaan narkoba pada pelajar tidak hanya merupakan masalah individu, tetapi juga mencerminkan gap yang ada dalam sistem pendidikan dan sosial. Salah satu fenomena yang mencolok adalah kurangnya pemahaman dan kesadaran akan bahaya narkoba di kalangan pelajar (Ondigo et al, 2019). Banyak di antara mereka yang terpengaruh oleh budaya populer atau teman sebaya yang mempromosikan penggunaan narkoba sebagai sesuatu yang keren atau menghibur tanpa memperhatikan risiko yang terkait (Bano, 2021).…”
Section: Pendahuluanunclassified
“…Masalah lain yang berkaitan dengan fenomena ini adalah kurangnya pengawasan dan pemantauan terhadap lingkungan di sekitar pelajar (Pyrkosch et al, 2022). Peran orang tua, guru, dan masyarakat dalam mendeteksi dan mencegah penyalahgunaan narkoba sering kali kurang optimal, sehingga banyak pelajar yang terjerumus ke dalam lingkungan yang mendukung atau memfasilitasi penggunaan narkoba tanpa adanya intervensi yang tepat waktu (Ondigo et al, 2019). Selain itu, masalah stigma juga menjadi hambatan dalam penanganan penyalahgunaan narkoba di kalangan pelajar (Shupp et al, 2020).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…In the Korogocho slums, Ondigo, Birech, and Gakuru [10] found that marijuana, miraa, alcohol, and cigarettes, according to the report, are the most often overused drugs among secondary school students, and they have ruined their core values, affecting their social skills growth and academic performance. Slum living, peer pressure, traffic, and poverty are all variables that lead to drug and substance addiction among students, according to the survey.…”
Section: The Concept Of Disciplinementioning
confidence: 99%
“…Many situations are cited as the causes of problematic behaviors in schools. Drugs and substance abuse (Ondigo, Birech & Gakuru, 2019), student alienation (Mau,1989), bullying (Salmon, James & Smith, 1998), school violence (Henry, 2000) are some of them. School burnout is one of these negative situations mentionedin the relevant literature (Gabola et al 2021).…”
Section: Introductionmentioning
confidence: 99%